Prevalence of ectopic eruption in first permanent molar in 8 years old Tehran school children - Afshar H; Nakhjavani Y; Akhavan P (Tehran University of Medical Sciences, 1999)
In this study, by cluster simple random sampling, the prevalence of ectopic of first permanent molar in 8 years old Tehran school children is considered and determined as 0.87 percent The involvement of maxilla was more than mandible and the difference was significant. Bilateral involvement was more than unilateral and boys were more- than girls, how ever the differences were not significant."nAs for as the geographical distribution is considered, the differences were not noticeable, either.